Prediction of ternary fluorooxoborates with coplanar triangular units [BOxF3−x]x− from first-principles. Issue 17 (14th April 2020) - Wei, Zhonglei; Zhang, Wenyao; Zeng, Hao; Li, Hao; Yang, Zhihua; Pan, Shilie
Abstract : From first-principles prediction, we got all the basic structural units of fluorooxoborates, namely, tetrahedral elements [BO x F4− x ] ( x = 1, 2, 3) like [BO4 ] and triangular elements [BO x F3− x ] ( x = 1, 2) like [BO3 ]. Abstract : Ten new ternary fluorooxoborate structures (B2 O2 F2, I–X) were obtained from first-principles prediction. Coplanar aligned triangular structural units [BO2 F] 2− and [BOF2 ] − like [BO3 ] 3− in borates were found from computational simulation. We identified new covalent coordination patterns of the F atom connected with the B atoms which were located in the bridging site, –B–F–B–. Besides, one molecular crystal with the [B4 O4 F4 ] molecular unit was attached.